A review of the reliability of land bank institution in Indonesia for effective land management of public interest. (September 2022) - Roestamy, Martin; Martin, Abraham Yazdi; Rusli, Radif Khotamir; Fulazzaky, Mohamad Ali
Abstract: It is not easy to get a decent housing for low-income people (LIP) in the cities of Indonesia due to the limitation of land available for development in the urban areas allows the speculators to retain the benefits of land in an unregulated commodity business. This study aims to examine and analyze the establishment of land bank for ensuring the implementation of more prosperous, fair sharing and sustainable land management. The observational method of reviewing the land use issues, land bank models and legal basis was performed to understand the eligibility of land bank in management of land use to serve public interest of infrastructure construction and development of affordable housing for LIP in urban areas. The establishment of land bank institution in Indonesia is considered important to accommodate the need of lands in urban areas for a wide array of purposes. The analysis of landless housing prices in the Jabodetabek region for the development of five-story residential building can save more than 50% of income toward the necessity of affordable housing for LIP. The finding of this study may provide a contribution to get better understanding on the decision making process of sustainable land management at all levels of government in Indonesia particularly by the provincial government of Special Capital Territory of Jakarta. Highlights: The issues of land and housing prices in Indonesia were reviewed. The establishment of land bank institutions was proposed to manage the lands. Various types of land supply can be transferred to the land bank management system. Landless housing prices in Jabodetabek were simulated to support decision making process.